The Effectiveness of Metacognitive Therapy on Psychological Capital, Marital Commitment, and Cognitive Emotion Regulation in Women Affected by Spousal Infidelity - Karimaee, Mitra; Aleyasin, Sayyed Ali; Heidari, Hassan; Davoudi, Hossein (International Journal of Education and Cognitive Sciences, 2024)
Purpose: The aim of this study was to evaluate the effectiveness of metacognitive therapy on psychological capital, marital commitment, and cognitive emotion regulation in women affected by spousal infidelity. Methods and Materials: This research was applied in its objective and quasi-experimental in method, utilizing a pretest-posttest design with a control group. The statistical population included all women affected by spousal infidelity who attended psychotherapy and counseling clinics in Tehran in 2023. From this population, 30 individuals were selected using convenience sampling. Participants completed the Luthans Psychological Capital Questionnaire (2007), the Adams and Jones Dyadic Commitment Inventory (DCI; 1997), and the Garnefski and Kraaij Cognitive Emotion Regulation Questionnaire (QERQ-short; 2006) in the pretest phase. The sample was then divided into an experimental group and a control group. The experimental group participated in eight 90-minute sessions of metacognitive therapy, while the control group received no intervention. After completing the sessions, participants again responded to the questionnaires, and a follow-up phase was conducted three months later. The data were analyzed using repeated-measures ANOVA with SPSS version 26. Findings: The results indicated that the F-statistic for psychological capital, with a significance level of .000, was smaller than the .05 error threshold, indicating a significant difference between the mean scores of the two groups. Thus, it was concluded that metacognitive therapy significantly affected psychological capital in women affected by spousal infidelity. Moreover, the lack of a significant difference between the mean scores in the posttest and follow-up phases demonstrated that the effectiveness of metacognitive therapy on psychological capital was sustained over time. Similarly, the F-statistic for marital commitment, which was smaller than the .05 error threshold, indicated a significant difference between the mean scores of the two groups. This finding suggested that metacognitive therapy significantly improved marital commitment in women affected by spousal infidelity. Additionally, no reduction in effectiveness was observed in the follow-up phase compared to the posttest, showing the sustained impact of the therapy on marital commitment. Finally, the F-statistic for cognitive emotion regulation was also smaller than the .05 error threshold, indicating a significant difference between the mean scores of the two groups. Conclusion: It was concluded that metacognitive therapy significantly improved cognitive emotion regulation in women affected by spousal infidelity. Furthermore, the effectiveness of the therapy on cognitive emotion regulation was not significantly reduced in the follow-up phase, demonstrating its lasting impact.